El Excentrico, 1957-05-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
May 20, 1957 [20 de mayo de 1957]. Ano 7, No. 18. Cover contains a photo of dancer, Ida Mae Cabral, in formal Spanish dance attire. The headline reads, "Miss Ida Mae Cabral. Outstanding Young Spanish Dancer."